2008
DOI: 10.1007/s00520-008-0524-z
|View full text |Cite
|
Sign up to set email alerts
|

The palliative performance scale: examining its inter-rater reliability in an outpatient palliative radiation oncology clinic

Abstract: PPS was shown to have good overall inter-rater reliability in an outpatient palliative setting, but more research is needed to establish the validity and reliability of the tool in a variety of different palliative settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 20 publications
(35 reference statements)
0
27
0
3
Order By: Relevance
“…For the PPS, inter-rater agreement has only been compared in one clinical study [6], which found better correlation between scores rated by a physician and research assistant (Spearman rank correlation, r=0.86) than between the physician and radiation therapist (r=0.77). The reliability and validity of the PPS was recently assessed using web-based scenarios; two combined groups of physicians and nurses rated PS based on 11 scenarios, and the ratings of the two groups were compared [26].…”
Section: Discussionmentioning
confidence: 98%
“…For the PPS, inter-rater agreement has only been compared in one clinical study [6], which found better correlation between scores rated by a physician and research assistant (Spearman rank correlation, r=0.86) than between the physician and radiation therapist (r=0.77). The reliability and validity of the PPS was recently assessed using web-based scenarios; two combined groups of physicians and nurses rated PS based on 11 scenarios, and the ratings of the two groups were compared [26].…”
Section: Discussionmentioning
confidence: 98%
“…The scale has eleven levels, from zero to 100%, divided in intervals of 10. A 100% level means that the patient is fully functional, and zero means death 15 .…”
Section: Methodsmentioning
confidence: 99%
“…Although interrater reliability has been validated for the CFS and the PPS, interrater reliability of the scores assigned was established to ensure the accuracy of the scores for the conversion chart. Interrater reliability within each measure was determined by comparing the scores that nurses and physicians within each specialty assigned.…”
Section: Methodsmentioning
confidence: 99%